2020
DOI: 10.3390/jcm9061751
|View full text |Cite
|
Sign up to set email alerts
|

Role of Advanced Glycation End Products on Aortic Calcification in Patients with Type 2 Diabetes Mellitus

Abstract: The aim of this study was to evaluate the relationship between serum levels of advanced glycation end products (AGEs) and abdominal aortic calcification (AAC) in patients with type 2 diabetes mellitus (DM2). This was a prospective cross-sectional study. One-hundred and four consecutive patients with DM2 were given lateral lumbar X-rays in order to quantify abdominal aortic calcification (AAC). Circulating levels of AGEs and classical cardiovascular risk factors were determined. Clinical history was also regist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…2a ). Studies have demonstrated that the AGE-RAGE signaling pathway is closely associated with the pathogenesis of diabetic vascular calcification 1 , 6 . So, we chose AGE-RAGE signaling pathway-associated proteins for further study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2a ). Studies have demonstrated that the AGE-RAGE signaling pathway is closely associated with the pathogenesis of diabetic vascular calcification 1 , 6 . So, we chose AGE-RAGE signaling pathway-associated proteins for further study.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms have been raised to state how AGEs accelerate atherosclerotic calcification in diabetes. On the one hand, chronically elevated hyperglycemia markedly accelerated the AGEs production 6 , on the other hand, hyperglycemia specifically impaired the clearance of AGEs 38 . Excessive accumulation of AGEs activates RAGE, and accelerates atherosclerotic calcification by modifying phenotype switch of VSMC from contractile to osteoblastic phenotype, apoptosis and MV release 11 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also leads to an increase in the production and accumulation of AGEs in the existing tissue, which contributes to the current situation. Sanchis et al and Deng et al also blamed this mechanism in their studies, which showcased the relationship between aortic valve calcification and serum AGE levels [ 28 , 29 ]. We also believe that the increase in AGE levels in our study affects the development of MAC by using similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%